(untitled) (Indian Journal of Animal Production and Management, 2024)
A survey-based study was conducted to know the existing cattle and buffalo breeding practices followed by the tribal livestock farmers of North Gujarat region. For the study, two villages from 7 taluka of three districts of North Gujarat region were selected having large number of tribal farmers. Fifteen respondents were selected from each village, which resulted into selection of 210 respondents for the study. Data were collected with the help of a well-structured pretested interview schedule. Frequency was obtained from each category and percentage of respondents was calculated to draw the inference. Study revealed that mucus discharge and bellowing (76.19%) signs were the major symptoms utilized for the detection of oestrous. For the breeding of their cows 72.73 per cent respondents utilized artificial insemination and 61.50 per cent bred buffaloes by natural service. More than one third respondents (35.24%) bred their animals between 12 to 18 hours after heat detection. More than fifty percent (56.19 %) respondents adopted pregnancy diagnosis of their animals. Majority of the respondents (74.29%) were conscious of breeding their cows within a range of 5 months after calving. The findings of this study revealed that the most of the respondents involved in cattle and buffalo husbandry had adopted artificial insemination but still a notable number of farmers preferred natural service in tribal area.